Cardiac fibrosis in the ageing heart: Contributors and mechanisms - Lu, L.; Guo, J.; Hua, Y.; Huang, K.; Magaye, R.; Cornell, J.; Kelly, D.; Reid, Christopher; Liew, D.; Zhou, Y.; Chen, A.; Xiao, W.; et al. (Wiley-Blackwell Publishing Asia, 2017)
© 2017 John Wiley & Sons Australia, Ltd. Cardiac fibrosis refers to an excessive deposition of extracellular matrix (ECM) in cardiac tissue. Fibrotic tissue is stiffer and less compliant, resulting in subsequent cardiac dysfunction and heart failure. Cardiac fibrosis in the ageing heart may involve activation of fibrogenic signalling and inhibition of anti-fibrotic signalling, leading to an imbalance of ECM turnover. Excessive accumulation of ECM such as collagen in older patients contributes to progressive ventricular dysfunction. Overexpression of collagen is derived from various sources, including higher levels of fibrogenic growth factors, proliferation of fibroblasts and cellular transdifferentiation. These may be triggered by factors, such as oxidative stress, inflammation, hypertension, cellular senescence and cell death, contributing to age-related fibrotic cardiac remodelling. In this review, we will discuss the fibrogenic contributors in age-related cardiac fibrosis, and the potential mechanisms by which fibrogenic processes can be interrupted for therapeutic intent.